The influence of perceived social support on anxiety among international students: the mediating role of communicative adaptability - Song, Lili; Peng, Chundi; Hai, Yang; Wang, Jingya; Zhao, Jiyang (Frontiers in Psychology, 2026)
BackgroundAnxiety is one of the psychological problems that cannot be ignored among many international students. Long-term anxiety has a significant negative impact on the social life and academic achievement of international students. Without timely intervention, it may gradually escalate, induce extreme high-risk behaviors, and seriously threaten the life, health and safety of international students. This study aims to investigate the current situation of anxiety among international students, analyze the influence of perceived social support on anxiety among international students, and explore the mediating role of communicative adaptability.MethodsThis study was conducted in June 2024, and a convenience sampling method was used to investigate 198 international students in a university in Harbin. Measurements included a general demographic questionnaire, Depression Anxiety Stress Scale, Multidimensional Scale of Perceived Social Support, and Communicative Adaptability Scale. In this study, SPSS27.0 software was used to conduct descriptive statistical analysis, t test and variance analysis, correlation analysis and regression analysis. Meanwhile, PROCESS plug-in in SPSS27.0 software was used to test the mediation model.ResultsThe results of correlation analysis showed that perceived social support was positively correlated with communicative adaptability (r = 0.389, p < 0.01) and negatively correlated with anxiety (r = −0.325, p < 0.01). Communicative adaptability was negatively correlated with anxiety (r = −0.250, p < 0.01). The mediating effect of communicative adaptability was significant in perceived social support on anxiety (95% CI: −0.131 to −0.013).ConclusionProviding more adaptive and targeted social support and cultural adaptation activities may effectively alleviate the anxiety level of international students, and thus maintain and improve the mental health of international students.